2020
DOI: 10.1021/jacs.0c09403
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Amination: Diazirines as Single and Double Electrophilic Nitrogen Transfer Reagents

Abstract: The ubiquity of nitrogen-containing small molecules in medicine necessitates the continued search for improved methods for C–N bond formation. Electrophilic amination often requires a disparate toolkit of reagents whose selection depends on the specific structure and functionality of the substrate to be aminated. Further, many of these reagents are challenging to handle, engage in undesired side reactions, and function only within a narrow scope. Here we report the use of diazirines as practical reagents for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…demonstrated that NHPI esters can couple with electrophilic aziridines under iron catalysis (Scheme 90). [374] A variety of NHPI esters are amenable to this transformation, but primary substrates could only be coupled with C 8 F 17 ‐substituted diazirine. The obtained diaziridines can be further converted to amines, hydrazines, and nitrogen‐containing heterocycles.…”
Section: Decarboxylative C−pnictogen Bond Formationmentioning
confidence: 99%
“…demonstrated that NHPI esters can couple with electrophilic aziridines under iron catalysis (Scheme 90). [374] A variety of NHPI esters are amenable to this transformation, but primary substrates could only be coupled with C 8 F 17 ‐substituted diazirine. The obtained diaziridines can be further converted to amines, hydrazines, and nitrogen‐containing heterocycles.…”
Section: Decarboxylative C−pnictogen Bond Formationmentioning
confidence: 99%
“… 46 50 The most commonly encountered diazirines are the trifluoromethyl derivatives, which are often applied as photoaffinity probes in biological applications. 51 , 52 However, importantly for our purposes, the corresponding α-chlorodiazirines ( 1 ) are much more easily prepared than their trifluoromethyl analogues via the single-step Graham oxidation of amidine precursors ( Figure 1 C). 53 , 54 Simple treatment with bleach directly affords a diverse range of chlorodiazirines (see the experimental Supporting Information (SI) for details).…”
mentioning
confidence: 99%
“…This particular reactivity has been exploited in cross‐coupling reactions with aryl halides [3] or boronic acids, [4] and for the generation of sulfur ylides which are useful intermediates in synthetic chemistry [5] . Recently, Lopchuk and co‐workers elegantly demonstrated that diazirines could serve as effective electrophilic nitrogen transfer reagents in the decarboxylative amination of redox‐active esters [6] . On the other hand, diazirine occupies a privileged position in photoaffinity labeling of biomolecules, which has received a considerable attention in chemical biology for providing new insights into biological mechanisms, as well as in medicinal chemistry for identifying protein‐protein interactions and biological targets of small‐molecule ligands [7] .…”
Section: Introductionmentioning
confidence: 99%